2018
DOI: 10.1071/ch18117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ionic Liquids on the Hatching of Artemia salina Cysts

Abstract: We investigated the effect of six ionic liquids (ILs), and dimethylsulfoxide (DMSO) as a typical molecular liquid (organic solvent), on the hatching of Artemia salina cysts. The effect of an IL on the hatching of Artemia salina strongly depends on the specific combination of cation and anion. Of the ILs tested, choline acetate and choline chloride had a significantly lower toxicity. The level of inhabitation followed the order [chl][dhp] > [bmim][NO3] > [MAN][NO3] > [bmim][Ac] > DMSO > [chl][Ac]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 42 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Artemia salina has also been used in the toxicological study of ILs, Bioucas et al [ 130 ] observed that [C 2 mim][CH 3 SO 3 ] (LC 50 = 4.834 mg·L −1 ) was more toxic than ethylene glycol, and this IL could be classified as highly toxic, although authors suggest that more studies are needed for a better analysis of [C 2 mim][CH 3 SO 3 ] toxicity. The brine shrimp lethality test (BSLT) was used to determine the toxicity of several ILs on Artemia salina cysts [ 131 ]. It was observed that an increase of IL concentration provoked decreased Artemia salina hatchability.…”
Section: Effect Of Ionic Liquids On Animalsmentioning
confidence: 99%
“…Artemia salina has also been used in the toxicological study of ILs, Bioucas et al [ 130 ] observed that [C 2 mim][CH 3 SO 3 ] (LC 50 = 4.834 mg·L −1 ) was more toxic than ethylene glycol, and this IL could be classified as highly toxic, although authors suggest that more studies are needed for a better analysis of [C 2 mim][CH 3 SO 3 ] toxicity. The brine shrimp lethality test (BSLT) was used to determine the toxicity of several ILs on Artemia salina cysts [ 131 ]. It was observed that an increase of IL concentration provoked decreased Artemia salina hatchability.…”
Section: Effect Of Ionic Liquids On Animalsmentioning
confidence: 99%
“…(issue 7, 2018) on the effect of ionic liquids on Artemia salina by Yoshimura and Shimizu also makes an important contribution to the understanding of ionic liquid interaction with the biosphere. [7] Application studies include papers from Watanabe et al on the development of glyme solvate ionic liquids for lithium batteries, [8] while Pringle and her co-workers describe the use of ionic liquids for thermocells, demonstrating that incorporation of various ionic liquids enhance the electrochemical and mechanical properties as well as thermal energy harvesting performance. [9] Demonstrating the continued impact of this field in the area of catalysis, Schroeder and her group at TUWien report on the application of surface-active ionic liquids in catalytic water splitting, [10] while Chrobok and her team, involving collaborators in Poland, QUILL, and Monash, apply protic ionic liquids based on oligomeric anions as catalysts and solvents for e-caprolactam synthesis.…”
mentioning
confidence: 99%